(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Vehicles with hybrid drive systems are characterized by their driving dynamics, their energy efficiency and their environment-friendliness especially. Dependent on the electrical power and the drive train structure these hybrid drives are grouped into different classes. Designations such as micro-hybrid, mild- hybrid, full-hybrid, serial-hybrid, serial/parallel-hybrid or power-split-hybrid reflect the large variance of these different drive train possibilities. In hybrid drive systems electronically controlled converters take an important role. With such a converter also the energy exchange between electrical power system and electrical machine is regulated. The reduction of the vehicle fuel consumption here is of special interest. Today's hybrid vehicles use for the control mainly information from the present driving conditions, taking into account the actual electrical power system-charge as well as the power demand of the driver. With such a control already considerable fuel reductions are reached. But additionally superimposed control and information systems promise substantial potential for more fuel reduction. With these systems an outstanding energy-saving and anticipatory way of driving could be realized. The aim is to find the best operating point in each case for the combustion engine and to adapt the charge state of the electrical power system to the respective driving situation.